2016
DOI: 10.4103/0971-4065.156115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of chronic kidney disease in newly diagnosed human immunodeficiency virus patients in Owerri, Nigeria

Abstract: Human immunodeficiency virus (HIV) infection is a common cause of chronic kidney disease (CKD) in Sub-Saharan Africa. This study aims at identifying the prevalence and predictors of CKD in newly diagnosed HIV patients in Owerri, South East Nigeria. This was a cross-sectional study consisting of 393 newly diagnosed HIV-seropositive subjects and 136 age- and sex-matched seronegative subjects as controls. CKD was defined as 24-hour urine protein (24-HUP) ≥0.3 g and/or glomerular filtration rate (GFR) < 60 ml/min.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
(40 reference statements)
6
18
1
1
Order By: Relevance
“…However, the study did not assess CD4 different levels, differing from this study. Renal diseases are common in HIV infection and tend to increase with HIV disease progression, influenced by different levels of immunosuppression [15,26]. However, this study has demonstrated variable association between proteinuric renal damage and different levels of immunosuppression.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…However, the study did not assess CD4 different levels, differing from this study. Renal diseases are common in HIV infection and tend to increase with HIV disease progression, influenced by different levels of immunosuppression [15,26]. However, this study has demonstrated variable association between proteinuric renal damage and different levels of immunosuppression.…”
Section: Discussionmentioning
confidence: 54%
“…Clear instructions were given to all the subjects on how to collect 24 h urine sample. For each participant, day-time blood samples and spot urine samples were collected at the end of the 24 h urine sample collection [8,[14][15][16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from Msango's work in Tanzania, which had a prevalence of 63.7% [9] higher than ours, all similar work in Africa had found prevalence equal to or lowers than our result. Ekat in Brazzaville [5], Anyabolu in Nigeria [10] found a prevalence of 42% and 22.5% respectively. The difference in methodology is the main explanation for this great variability of prevalence in these different works.…”
Section: Discussionmentioning
confidence: 99%
“…However, multi-linear regression analysis showed SUCr was not a predictor of proteinuria. SUCr is known to vary over 24 hours of the days and may not indicate quantitatively the presence of renal damage [ 16 ].…”
Section: Discussionmentioning
confidence: 99%